2023
DOI: 10.2147/jhc.s411806
|View full text |Cite
|
Sign up to set email alerts
|

Application and Resistance Mechanisms of Lenvatinib in Patients with Advanced Hepatocellular Carcinoma

Abstract: Lenvatinib, a multitargeted tyrosine kinase inhibitor (TKI), is one of the preferred targeted drugs for the treatment of advanced hepatocellular carcinoma (aHCC). Since the REFLECT study showed that lenvatinib was noninferior to sorafenib in overall survival (OS), lenvatinib monotherapy has been widely used for aHCC. Moreover, lenvatinib combination therapy, especially lenvatinib combined with immune checkpoint inhibitors (ICIs), has shown more encouraging clinical results. However, drug development and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…28 Furthermore, LVN can increase CD8+ T cell activity and reduce the number of myeloid-derived suppressor cells (MDSCs), thus also regulating the immune microenvironment. 18,[28][29][30] To obtain the most out of LVN, these antitumor mechanisms are adequately used and strengthened by combination therapy.…”
Section: The Clinical Pharmacological Character Of Lvn and Antitumor ...mentioning
confidence: 99%
“…28 Furthermore, LVN can increase CD8+ T cell activity and reduce the number of myeloid-derived suppressor cells (MDSCs), thus also regulating the immune microenvironment. 18,[28][29][30] To obtain the most out of LVN, these antitumor mechanisms are adequately used and strengthened by combination therapy.…”
Section: The Clinical Pharmacological Character Of Lvn and Antitumor ...mentioning
confidence: 99%
“…Recent studies have shown that epigenetics, transport processes, regulated cell death, tumor microenvironment, hypoxia and viral reactivation play a role in the production and development of sorafenib resistance in HCC ( Tang et al, 2020 ; Ladd et al, 2024 ). Lenvatinib resistance also has a similar mechanism to sorafenib resistance, including noncoding RNA regulation, tumor immune microenvironment and expansion of cancer stem cells ( Tao et al, 2023 ). In addition, the combination of immune checkpoint inhibitors (ICI) and TKIs has important therapeutic significance in the treatment of HCC ( Starzer et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%